Implementation of Molecular Systems for Identification of Genetic Polymorphism in Winter Wheat to Obtain High-Performance Special Varieties - Morgun, B.V.; Stepanenko, A.I.; Stepanenko, O.V.; Bannikova, M.O.; Holubenko, A.V.; Nitovska, I.O.; Maystrov, P.D.; Grodzinsky, D.M. (Science and Innovation, 2024)
Molecular genetic systems for polymorphism detection to screen the presence of alleles in 100 winter wheat varieties have been designed. Polymerase chain reactions (PCR) have been carried out to identify the relevant genes. The level of spread of alleles related to low and medium activity of polyphenoloxidase (PPO) enzymes has been defined and the validation has been performed. The wheat varieties carrying 1AL.1RS, 1BL.1RS rye translocations and those containing the Tamyb10 gene recessive allele and the Stb4 gene responsible for resistance to Septoria linked to Xgwm111 polymorphic locus have been identified. The waxy wheat and other varieties carrying atypical functional Wx-B1e allele have been determined. One hundred elite and promising wheat varieties have been characterized depending on the presence of alleles of genes determining the grain qualities (PPO, Tamyb10-A1, and Wx genes) and resistance to biotic and abiotic stresses (rye translocative material, Tamyb10-A1, Stb4).